Bringing an emphasis on technical writing to a freshman course in electrical engineering - Palmquist, Mike, author; Lile, Derek, author; Jayasumana, Anura, author; Mahan, John E., author; IEEE, publisher (Colorado State University. Libraries, 2000)
We have recently added a strong writing component to one of our freshman courses in electrical engineering. The students prepared two kinds of reports—memoranda and formal engineering project reports. Our instructional objectives were to execute well these two forms: to write with a professional tone, and to make good choices about which technical material to include. To meet these objectives, model memos and engineering project reports were developed, lectures about these memos and reports were presented, a Web site for the course was developed, the technical aspects of the reports were graded by a student hourly grader, the writing aspects of the reports were evaluated by a professor, and followup debriefings were conducted at the lecture class meetings. We report on the development process and discuss student response to the course.
Keywords: technical reports; writing; electrical engineering education; engineering writing; technical writing; freshman; project report